2015
DOI: 10.1007/s00380-015-0677-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sustained release of basic fibroblast growth factor using gelatin hydrogel in patients with critical limb ischemia

Abstract: As a form of therapeutic angiogenesis, we sought to investigate the safety and efficacy of a sustained-release system of basic fibroblast growth factor (bFGF) using biodegradable gelatin hydrogel in patients with critical limb ischemia (CLI). We conducted a phase I-IIa study that analyzed 10 CLI patients following a 200-μg intramuscular injection of bFGF-incorporated gelatin hydrogel microspheres into the ischemic limb. Primary endpoints were safety and transcutaneous oxygen pressure (TcO2) at 4 and 24 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…In our study, lower FGF-2 levels are associated with the appearance of new plaques, but were not associated with the baseline presence of atheroma plaques, agreeing with the notion of a protective role for FGF-2 in the early stages of atheroma plaque formation. Indeed, clinical trials using FGF-2 as a treatment for revascularization have not shown any effect aggravating atherosclerotic disease (46,47). Our results disclosing a higher odds ratio (OR) for atheromatosis progression in patients with CKD stages 4-5 and on dialysis than in patients with CKD stage 3 may appear discordant with those of Rigatto et al (48) observing lower progression of atheromatosis in later CKD stages.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, lower FGF-2 levels are associated with the appearance of new plaques, but were not associated with the baseline presence of atheroma plaques, agreeing with the notion of a protective role for FGF-2 in the early stages of atheroma plaque formation. Indeed, clinical trials using FGF-2 as a treatment for revascularization have not shown any effect aggravating atherosclerotic disease (46,47). Our results disclosing a higher odds ratio (OR) for atheromatosis progression in patients with CKD stages 4-5 and on dialysis than in patients with CKD stage 3 may appear discordant with those of Rigatto et al (48) observing lower progression of atheromatosis in later CKD stages.…”
Section: Discussionsupporting
confidence: 77%
“…However, bFGF usually has a short half‐life (≈46 min) because of enzymolysis, and it easily and rapidly diffuses away from the injured site. This has forced investigators to introduce massive doses or frequent dosing of bFGF into the body, which risks systemic toxicity, possible renal failure, tumor growth, and poor patient compliance with increased cost . In recent years, more and more researchers have focused on developing localized controlled release bFGF delivery systems, which have fewer side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several growth factors, such as vascular endothelial growth factor(VEGF) [7][8][9][10][11][12], fibroblast growth factor (FGF) [7,13], hepatocyte growth factor (HGF) [14] and platelet-derived growth factor (PDGF), have been generated in the presence of MI to resist ischemia and irreversible heart death. As the loss is highly localized, the endogenous response may be insufficient to repair the damaged blood vessels.…”
Section: Introductionmentioning
confidence: 99%